DYNAMIC ANALYSIS OF BASEMENT COMPRESSOR (Municipal economy of cities. Series: «Economy science», 2013)
Analyzes the dynamic characteristics of the compressor base, calculated by mathematical modeling on a computer and regulatory literature.